2004
DOI: 10.1123/ijsnem.14.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Copper Biochemical Indices of Antioxidant Status in Elite Athletes of Different Modalities

Abstract: The purpose of this study was to compare zinc and copper biochemical indices of antioxidant status and their relationship in elite athletes of different modalities: aerobic with high-impact (triathletes, n = 10 and long-distance runners, n = 12), anaerobic with high-impact (short-distance runners, n = 9), and anaerobic with low-impact (short-distance swimmers, n = 13). The influence of recent dietary intake and body composition was also evaluated. A venous blood sample was drawn 16-20 hr after competition for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
1
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
0
30
1
11
Order By: Relevance
“…In fact, we observed no significant differences among short distance events (400m, 800m, 1500m) or among long distance athletes (5k, 10k, marathon, triathlon) for FORT and FORD across any of the time points measured. Although Koury et al (2004) observed no significant differences in antioxidant enzymes between elite short distance and long distance runners, they noted that the triathletes had significantly greater concentrations of superoxide dismutase in red blood cells than did both the other running groups. It is a limitation that we did not have a large enough number of triathletes to examine this further.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, we observed no significant differences among short distance events (400m, 800m, 1500m) or among long distance athletes (5k, 10k, marathon, triathlon) for FORT and FORD across any of the time points measured. Although Koury et al (2004) observed no significant differences in antioxidant enzymes between elite short distance and long distance runners, they noted that the triathletes had significantly greater concentrations of superoxide dismutase in red blood cells than did both the other running groups. It is a limitation that we did not have a large enough number of triathletes to examine this further.…”
Section: Discussionmentioning
confidence: 86%
“…Some authors believe that the magnitude of the copper loss through sweat justifies these alterations, although it does not lead to copper deficiency (14,(20)(21) . The several serum concentrations found by different studies (8,14) may be also partially explained by the chronic physical training which apparently stimulates antioxidant defense mechanisms, triggering the serum copper for cerulloplasmin and Cu-Zn SOD synthesis (22) .…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, it is possible that the increase in cerulloplasmin in response to the interleukins in the physical exercise is also associated with its role as antioxidant (22,26) . The cerulloplasmin concentration in the present study was sensitive to the serum copper concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations